Efficacy and survival prognosis analysis of surgical resection combined with targeted therapy in patients with colorectal cancer liver metastasis - Yan, Feihu; Shi, Yunjie; Kang, Zhengchun; Wang, Hantao; Li, Xu (Frontiers in Oncology, 2025)
IntroductionColorectal cancer liver metastasis (CRLM) is a leading cause of death in colorectal cancer patients. Simple surgical resection has a high recurrence rate, and combining targeted therapy offers a new way to improve prognosis. Currently, the efficacy of surgery combined with targeted therapy and the influencing factors of prognosis still require in-depth exploration.MethodsFrom January 2019 to February 2022, 76 CRLM patients were randomly split into an observation group (n=38, surgery + chemotherapy + bevacizumab-based targeted therapy) and a control group (n=38, surgery + conventional chemotherapy). Key indicators were compared, and Cox regression analyzed prognosis factors.ResultsThere were no significant differences in operation time (185.6±32.4 min vs. 178.9±29.5 min) or intraoperative blood loss (210.3±56.7 ml vs. 205.8±51.2 ml) between groups (P>0.05). However, the observation group had a shorter hospital stay (10.2±2.1 days vs. 12.5±2.6 days, P<0.05), higher ORR (68.9% vs. 46.7%) and DCR (91.1% vs. 75.6%, both P<0.05), and better 1-, 2-, 3-year PFS (72.2%/45.6%/31.1% vs. 51.1%/26.7%/15.6%) and OS (86.7%/64.4%/48.9% vs. 71.1%/42.2%/27.8%, all P<0.05). The observation group also had a higher hypertension rate (23.3% vs. 6.7%, P<0.05), with no other significant adverse reaction differences (P>0.05). Cox regression showed targeted therapy and ≤3 liver metastases were independent factors for favorable prognosis (P<0.05).DiscussionSurgical resection combined with targeted therapy can effectively improve tumor control efficacy and long-term survival outcomes of CRLM patients, and shorten the hospital stay. Although this combined regimen increases the risk of hypertension, its overall safety is controllable.